Accumulation and Endocrine Disrupting Effects of the Flame Retardant Mixture Firemaster® 550 in Rats: An Exploratory Assessment. Issue 2 (8th November 2012) - Patisaul, Heather B.; Roberts, Simon C.; Mabrey, Natalie; McCaffrey, Katherine A.; Gear, Robin B.; Braun, Joe; Belcher, Scott M.; Stapleton, Heather M.; Slitt, Angela L.; Hodgson, Ernest
ABSTRACT Firemaster® 550 (FM 550), a fire‐retardant mixture used in foam‐based products, was recently identified as a common contaminant in household dust. The chemical structures of its principle components suggest they have endocrine disrupting activity, but nothing is known about their physiological effects at environmentally relevant exposure levels. The goal of this exploratory study was to evaluate accumulation, metabolism and endocrine disrupting effects of FM 550 in rats exposed to 100 or 1000 µg/day across gestation and lactation. FM 550 components accumulated in tissues of exposed dams and offspring and induced phenotypic hallmarks associated with metabolic syndrome in the offspring. Effects included increased serum thyroxine levels and reduced hepatic carboxylesterease activity in dams, and advanced female puberty, weight gain, male cardiac hypertrophy, and altered exploratory behaviors in offspring. Results of this study are the first to implicate FM 550 as an endocrine disruptor and an obesogen at environmentally relevant levels. #x000A9; 2012 Wiley Periodicals, Inc. J BiochemMol Toxicol 27:124‐136, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/jbt.21439